Face exploration, emotion recognition, and emotional enhancement of memory in relapsing-remitting multiple sclerosis - Elisabeth Goettfried; Robert Barket; Ronen Hershman; Margarete Delazer; Michael Auer; Klaus Berek; Philipp Ellmerer; Barbara Seebacher; Harald Hegen; Franziska Di Pauli; Florian Deisenhammer; Laura Zamarian (PLoS ONE, 2025)
Background Recognizing familiar faces and identifying emotions through facial expressions are essential for social functioning. This study aimed to examine whether people with relapsing-remitting multiple sclerosis (PwMS) differ from healthy control individuals (HC) in their performance on different tasks related to facial emotion processing. Methods In a cross-sectional controlled study, 30 PwMS and 35 HC completed a baseline neuropsychological evaluation and experimental tasks assessing visual exploration of facial stimuli through eye tracking, facial emotion recognition, and facial memory recognition. The facial stimuli displayed either a neutral expression or an emotion (happiness, fear, or disgust). Results PwMS and HC performed comparably in facial emotion recognition. In facial memory recognition, HC were significantly more accurate in recognizing previously seen fearful faces compared to neutral faces (Wilcoxon test, Z = -2.26, P = 0.024), demonstrating emotional enhancement of memory. In contrast, PwMS did not exhibit a memory advantage for fearful faces over neutral faces (P > 0.05). Groups also differed in the eye-tracking task. In all but one condition (disgust), PwMS showed a significantly greater tendency to explore the eye area rather than the mouth area compared to HC. Conclusions Changes in visual exploration and a lack of emotional enhancement of memory are observed in PwMS, who otherwise demonstrate intact facial emotion recognition. These results suggest altered emotion-cognition interactions in PwMS. Early detection of subtle changes and targeted interventions may help prevent future debilitating impairments in social functioning.